Dinâmica de ocupação e comportamento de nidificação de Xylocopa frontalis (Olivier, 1789) (Apidae, Xylocopini) em abrigos artificiais - Pedroso, Henrique Lomônaco (2014)
This paper analyzed some aspects of the population dynamics and of the nesting behavior of Xylocopa frontalis (Olivier, 1789), popularly known as the carpenter bee. The patterns of colonization (occupation, philopatric and dispersive behavior, permanence period, use and reuse of the nests by emerging and vicinity females) of four bee-shelters in different environments (ecological reserve and farm), seasons (hot/cold and wet/dry) and conditions of nest supply (high and low amount of trap nests) were described. In each environment two shelters containing substrates for nest building were installed and the initial populations founded were individually marked and observed for a period of approximately one year. The proportion between the number of first-established nests and the reused ones did not differ between the shelters. There were a greater number of new foundations over the reuse of the nest regardless of the number of nests provided. The number of brood cells in the first-established nests was greater than that of the reused ones and the proportions of each of these categories did not differ between the bee-shelters. The similarity of the variation pattern in the number of females between shelters of the same area would indicate the influence of microclimatic factors governing the dynamic occupation of the bee-shelters and consequently the number of brood cells. In no shelter occurs the full utilization of the available nests and no differences in the number of offspring produced per female were found. In all shelters, the number of dispersing females was higher than the number of philopatric ones and the proportionality between these variables did not differ between the shelters. The maximum period oftime that a female remained in the bee-shelter was equivalent to 198 days. For the dispersing females, the minimum period of permanence in the bee-shelter was 12 days, with an average of 45 days. The nest use for females from the vicinities may contribute to maximize the population genetic variability of X. frontalis.